التغيرات الدموية في مستويات الهيموغلوبين و المتهيموغلوبين بعد التسمم بالنترات في دجاج اللحم - AL-Saadi, Raghad N.; Al-Sultan, Imad I. (The Iraqi Journal of Veterinary Medicine, 2021)
This study was aimed to understand the hematological changes in the level of Hb and Met-Hb which produced after potassium nitrate intake via water and feed to broiler chicks for 6 weeks and indifferent concentration also after stoppage for 4 weeks of nitrate intake. A number of 135 chicks one day old faobro breed were used. After two weeks aclimitiztiation ,chicks were separated in to seven groups , one was control and other six were given potassium nitrate in drinking water or in feed at 0.25, 0.5, 0.75 gm/ kg body weigh to each group. The results showed significant statistical in the Hb rates and the different nitrate concentrations used. Also there were significant differences in the 2nd week of the experiment and indicated a decrease in Hb concentrations. Statistical significant of difference was obvious in the groups fed on concentrations 0.25, 0.5 gm/ kg b.w. and in groups given nitrate in drinking water in concentrations 0.25, 0.5, 0.75 gm/kg b.w. There were significant statistical differences in Met-Hb rates formed and the amount of nitrate used and the weeks in all animal groups treated with nitrate which started at the 3rd week from the start of the experiment. The increase in the rates of Met-Hb indicate an important statistical differences or significances especially in groups fed 0.25 gm/kg b.w. nitrate concentration and in drinking water groups at 0.5 and 0.75 gm/kg b.w. concentrations. no significant statistical differences between the control group from week 8th till the week 10th of the experiment.